Papulopustular demodicosis: a case report - Mariyani, Sri; Etnawati, Kristiana (Universitas Gadjah Mada, 2023)
Primary demodicosis is an infestation of Demodex colonization >5 mites/cm2 without pre-existing or concomitant inflammatory skin disease. Primary demodicosis is divided into 3 variants i.e. spinulata, papulopustular and nodulocystic. Several topical and systemic agents are used in the Demodex facial treatment. A 22 y.o. man complained of acne on his face three months ago. On physical examination, there were pustules, multiple erythematous papules, ice pick atrophic scars, and box and rolling scars. KOH examination found the Demodex number > 5 mites/cm2. No spores were found. The patient received oral and topical metronidazole therapy. Papulopustular demodicosis is a follicular inflammation caused by Demodex mites. The inflammatory stage shows a predilection for the perioral, periorbital, and periauricular regions. According to the pattern of morphology and localization of the centrofacial area, some cases of demodicosis are often referred to as Rosacea-like (rosaceiform) demodicosis. The treatment goals are to reduce the overall number of mites and treat the underlying condition. This paper reports a case of papulopustular demodicosis of the face. The diagnosis was made by history taking and physical examination using the diagnostic criteria for demodicosis. Clinical improvement was obtained after oral and topical metronidazole therapy for two weeks.